101k views
3 votes
3(1-2x(=x-8(x-1)= Can someone please help me with this question.

User David Ma
by
4.8k points

1 Answer

3 votes

Answer:

x=5

Explanation:

3(1-2x)=x-8(x-1)

We simplify the equation to the form, which is simple to understand

3(1-2x)=x-8(x-1)

Reorder the terms in parentheses

+(+3-6x)=x-8*(x-1)

Remove unnecessary parentheses

+3-6x=+x-8+*(+x-1+)

Reorder the terms in parentheses

+3-6x=x+(-8x+8)

Remove unnecessary parentheses

+3-6x=+x-8x+8

We move all terms containing x to the left and all other terms to the right.

-6x-1x+8x=+8-3

We simplify the left and right sides of the equation.

+1x=+5

We divide both sides of the equation by 1 to get x.

x=5

______________

:) UR welcome

User Valerie Linc
by
4.7k points